HIV/AIDS-related hyponatremia: an old but still serious problem. (15th October 2018) - Shu, Zhanjun; Tian, Zimeng; Chen, Jinglin; Ma, Jianping; Abudureyimu, Aihemaiti; Qian, Qianqian; Zhuo, Li
Abstract: Hyponatremia is the most common electrolyte disorder in hospitals. Many medical illnesses, including congestive heart failure, liver failure, renal failure and pneumonia, may be associated with hyponatremia. In addition, hyponatremia in patients with the acquired immunodeficiency syndrome (AIDS) and AIDS-related complex (ARC) was first reported in 1993. The evidence suggests that severe hyponatremia is associated with increased morbidity and mortality in human immunodeficiency virus (HIV)/AIDS patients; however, the incidence of hyponatremic syndrome in HIV/AIDS patients remains very high in clinical practice, as almost 40% of HIV/AIDS inpatients in Xinjiang, a developing region of China, are hyponatremic. A method for identifying the pathogenesis and therapeutic treatments for hyponatremia in HIV/AIDS patients is needed. This review focuses on the clinical and pathophysiological aspects of hyponatremia and highlights the causes, presentation and treatment recommendations for hyponatremic patients with HIV/AIDS.